2016
DOI: 10.2131/jts.41.91
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of spindle checkpoint function in rats following 28 days of repeated administration of renal carcinogens

Abstract: We previously reported that 28-day exposure to hepatocarcinogens that facilitate cell proliferation specifically alters the expression of G1/S checkpoint-related genes and proteins, induces aberrant early expression of ubiquitin D (UBD) at the G2 phase, and increases apoptosis in the rat liver, indicating G1/S and spindle checkpoint dysfunction. The present study aimed to determine the time of onset of carcinogen-specific cell-cycle disruption after repeated administration of renal carcinogens for up to 28 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Only nitrofurantoin is a possible carcinogen due to its genotoxic and carcinogenic potential structures, despite its antimicrobial property [17,18,19,20]. In Kimura’s report (2016), nitrofurantoin does not exert sufficient renal carcinogen responses even after 28 days of administration [21]. In a recent study on the structure-related genotoxicity of nitrofurantoin, a new evidence revealed that nitrofurantoin does not increase the mutation frequency in the experimental mice.…”
Section: Discussionmentioning
confidence: 99%
“…Only nitrofurantoin is a possible carcinogen due to its genotoxic and carcinogenic potential structures, despite its antimicrobial property [17,18,19,20]. In Kimura’s report (2016), nitrofurantoin does not exert sufficient renal carcinogen responses even after 28 days of administration [21]. In a recent study on the structure-related genotoxicity of nitrofurantoin, a new evidence revealed that nitrofurantoin does not increase the mutation frequency in the experimental mice.…”
Section: Discussionmentioning
confidence: 99%